Daur Optimum Pemangkasan Daun Kayu Putih di KPH Yogyakarta (Jurnal Penelitian Kehutanan Wallacea, 2019)
The productivity of cajuput plantation has improved through tree breeding, while manipulation of site and management engineering of timber plantations have been less attention. Management engineering can be obtained by determining the optimum cycle of cajuput leaves harvesting. This study aims to determine the optimum cycling of cajuput leaves harvesting at KPH Yogyakarta by considering the biological cycles of cajuput leaves, chemical physical properties, and the yield of cajuput oil. The tools used in the research were digital scales, distillation devices, and testing tools of physical-chemical properties of cajuput oil. The material for research wasthe cajuput plantsat KPH Yogyakarta. Data of cajuput leave-twig biomass were obtained for 9 months from 9 plots which were well distributed on various ages. Biological cycle analysis uses curent monthly increment (CMI) and mean monthly increment (MMI) intersection approach. Analysis of the physical-chemical properties on cajuput oil refers to SNI 3954:2014 on cajuput oil. The results showed that the biological cycles of cajuput leaves were obtained 5 months after leaves harvesting. The chemical physical properties of cajuput oil that meet the requirements of SNI were achieved after the leaves are 7 months after harvested. The yield of cajuput oil which isabove 0.7% was obtained after the leaves are 8 months after harvested. Thus, the optimum cycle for harvestingof cajuput leaves in KPH Yogyakarta is after 8 months.
Keywords: Optimal cycle; cajuput plant; biomass; harvesting; cajuput oil content